Feasibility, Reliability, and Validity of the Turkish Version of the Esophageal-Atresia-Quality-of-Life Questionnaires to Assess Condition-Specific Quality of Life in Children and Adolescents Born with Esophageal Atresia - Soyer, Tutku; Arslan, Umut Ece; Ulukaya Durakbaşa, Çiğdem; Aydöner, Sinem; Boybeyi-Türer, Özlem; Quitmann, Julia H; Dingemann, Jens; Dellenmark-Blom, Michaela (Turkish Journal of Gastroenterology, 2021)
Background: This study reports the feasibility, validity and reliability of the Turkish versions of the Esophageal-Atresia–Quality-of-Life (EA-QOL) questionnaires, which were originally developed in Sweden and Germany. Methods: After translation from Swedish to Turkish and cognitive debriefings, 51 families of children aged 2 to 7 years (parent-report, 17-items) and 54 families of children 8 to 17 years (child and parent-report, 24-items) responded to the EA-QOL questionnaires and a validated generic HRQOL-instrument (PedsQL4.0). Medical records of patients and questionnaires were used to obtain clinical data. The Turkish version of the EA-QOL questionnaires were evaluated for feasibility (<5% missing item responses), reliability (internal consistency/retest reliability for 3 weeks) and validity (known-groups/concurrent/convergent). Level of significance was p<0.05. Results: Feasibility of the Turkish version of the EA-QOL questionnaires was good. Internal consistency of all scales was satisfactory, as were the level of agreements of EA-QOL scores between the field- and retest study. Known-group and concurrent validity were achieved since the EA-QOL questionnaires showed that esophageal symptoms and feeding difficulties were negatively associated with EA-QOL total scores in both age specific versions (child-and parent report), and respiratory symptoms in the version for EA children 2 to 7 years (parent-report). A higher number of respiratory symptoms decreased the EA-QOL total scores in both age groups (parent-report, p<0.05). Correlations between the EA-QOL total scores and PedsQL-4.0 total scores supported convergent validity.Conclusion: The Turkish version of the EA-QOL questionnaires are feasible, valid and reliable to assess condition-specific HRQOL in EA children.